The complete chloroplast genome of Eclipta prostrata L. (Asteraceae) - Park, Jee Young (Mitochondrial DNA B Resour, 2016)
Eclipta prostrata is an herbal medicinal plant belonging to the Asteraceae family. In this study, complete chloroplast genome sequence of the E. prostrata was characterized by de novo assembly using whole genome sequence data. The genome of E. prostrata was 151,757 bp in length, which was composed of large single copy region of 83,285 bp, small single copy region of 18,346 bp and a pair of inverted repeat regions of 25,063 bp. The genome harboured 80 protein coding sequences, 30 tRNA genes and 4 rRNA genes. We confirmed close taxonomic relationship between E. prostrata and Helianthus annuus through phylogenetic analysis with chloroplast protein-coding genes.